Effect of gamma irradiation on caprolactam migration from multilayer polyamide 6 films into food simulants: Development and validation of a gas chromatographic method - Félix, Juliana S. [UNESP]; Monteiro, Magali [UNESP]; Manzoli, Jose E.; Padula, Marisa (Oxford University Press (OUP), 2010)
A GC method to determine caprolactam in water, 15% ethanol, and olive oil food simulants was developed and validated. Linear ranges varied from 0.96 to 642.82 μg/mL for water, 0.64 to 800.32 μg/mL for 15% ethanol, and 1.06 to 1062.34 μg/g for olive oil, with correlation coefficients higher than 0.999. Method precision studies showed RSD values lower than 5.45%, while method accuracy studies showed recovery from 72 to 111% for all simulants. The effect of gamma irradiation on caprolactam migration from multilayer polyamide 6 (PA-6) films intended for cheese into water, 15% ethanol, olive oil, and 3% acetic acid simulants was also studied. For migration assay, non-irradiated and irradiated (12 kGy) films were placed in contact with the simulant and exposed at 40°C for 10 days. The validated method was used to quantify caprolactam migration from multilayer PA-6 films into the simulants, which ranged from 1.03 to 7.59 mg/kg for non-irradiated films, and from 4.82 to 11.32 mg/kg for irradiated films. Irradiation caused almost no changes in caprolactam levels, with the exception of olive oil, which showed an increase in the caprolactam level. All multilayer PA-6 films were in accordance with the requirements of the legislation for caprolactam migration.